Structure‐Dependent Anchoring of Organic Molecules to Atomically Defined Oxide Surfaces: Phthalic Acid on Co3O4(111), CoO(100), and CoO(111). Issue 15 (2nd March 2016) - Xu, Tao; Schwarz, Matthias; Werner, Kristin; Mohr, Susanne; Amende, Max; Libuda, Jörg
Abstract: We have performed a model study to explore the influence of surface structure on the anchoring of organic molecules on oxide materials. Specifically, we have investigated the adsorption of phthalic acid (PA) on three different, well‐ordered, and atomically defined cobalt oxide surfaces, namely 1) Co3 O4 (111), 2) CoO(111), and 3) CoO(100) on Ir(100). PA was deposited by physical vapor deposition (PVD). The formation of the PA films and interfacial reactions were monitored in situ during growth by isothermal time‐resolved IR reflection absorption spectroscopy (TR‐IRAS) under ultrahigh vacuum (UHV) conditions. We observed a pronounced structure dependence on the three surfaces with three distinctively different binding geometries and characteristic differences depending on the temperature and coverage. 1) PA initially binds to Co3 O4 (111) through the formation of a chelating bis‐carboxylate with the molecular plane oriented perpendicularly to the surface. Similar species were observed both at low temperature (130 K) and at room temperature (300 K). With increasing exposure, chelating mono‐carboxylates became more abundant and partially replaced the bis‐carboxylate. 2) PA binds to CoO(100) in the form of a bridging bis‐carboxylate for low coverage. Upon prolonged deposition of PA at low temperature, the bis‐carboxylates were converted into mono‐carboxylate species. In contrast, the bis‐carboxylate layer was very stable at 300 K. 3) For CoO(111) we observed a temperature‐dependent change in the adsorption mechanism. Although PA binds as a mono‐carboxylate in a bridging bidentate fashion at low temperature (130 K), a strongly distorted bis‐carboxylate was formed at 300 K, possibly as a result of temperature‐dependent restructuring of the surface. The results show that the adsorption geometry of PA depends on the atomic structure of the oxide surface. The structure dependence can be rationalized by the different arrangements of cobalt ions at the three surfaces. Abstract : Surface structure matters : The adsorption geometry of phthalic acid is dependent on the atomic structure of the cobalt oxide surface. The structure dependence can be rationalized by the different arrangements of the cobalt ions at the three surfaces (see figure; IRAS=IR reflection absorption spectroscopy).